Midwives Care for Ny. B Babies with Low Birth Weight in The Pordomuan I Work Area, Teluk Pulai Village, Help the Puskesmas, Kualuh Leidong District - Andriani, Fitri; Lumban Gaol, Masta (International Journal of Nursing and Midwifery Research, 2023)
Every Indonesian child has the right to receive health services as written in Law no. 36 of 2009 article 131 paragraph 1 Efforts for infant and child health must be aimed at preparing future generations who are healthy, intelligent and qualified and to reduce infant and child mortality rates. LBW babies are babies born with a body weight of less than 2500 grams regardless of gestational mass. The level of morbidity and mortality in neonates depends not only on body weight, but also on the level of malnutrition of the baby itself. The causes of LBW are generally multifactorial, the most common cause of LBW is premature birth. The younger the gestational age, the greater the short-term and long-term risks that can occur.